(untitled) (k:ON - Kölner Online Journal für Lehrer*innenbildung, 2025)
The aim of this article is to present a broad spectrum of didactic objectives and methodological implementation options for incorporating the family languages of primary school children into the classroom in a way that is conducive to learning for all children. The starting point is the didactic functions as a theoretical result of the DFG-funded [anonymized]-study on the beliefs of primary school teachers on dealing with multilingualism. Based on this, concrete teaching ideas are described, including how the respective didactic goals can be achieved and with which methods.